O cidadão e a Poronga: a peleja de Vicente Salles contra a exclusão do negro da história do Pará - Souza, Roseane Silveira de (2014)
This dissertation is founded on the life journey of Vicente Juarimbu Salles (1931 2013), an anthropologist, historian and folklorist of Pará, Brazil, and on his pioneering studies about the African descendant s presence in Pará s History. This research is circumscribed to the Cultural History s realm, in the line of Culture and Representation. It aims to identify how this theme is intertwined to Vicente Salles life history, relying on his historiography as the object of study concerning the subjects who were excluded from History. The investigation s accomplishment counted on interviews with the author, his family members, friends and scholars who research the African descendant s culture. Readings and interpretations were also conducted through Salles work books and titles from the Author s series MicroEdição , as well as his correspondence with several interlocutors. From these sources it was possible to collect the historian s childhood, youth and adult life data in both personal and professional spheres, which try to show how this intellectual built a view over the subjects placed in the margins of History, like the African descendants in Amazon. The work approaches his first steps in Pará s research, encouraged by the local poet and folklorist Bruno de Menezes and by Edison Carneiro, an anthropologist from Bahia. Later on, it encompasses the project development in the Academic sphere at the National Philosophy Faculty of Brazil s University in Rio de Janeiro, but overall, at the Campaign in Defense of Brazilian Folklore, in which Salles worked from 1961 to 1972. The research also approaches the theoretical scenery of Social Sciences and Humanities, that were undergoing transformation in the 1960 s decade, when Salles developed the investigation resulting in the work: The African descendant in Pará: under the slavery regimen, that showed that the African descendant, contrary to an imperative vision of those times, was remarkably important to the formation of Pará s society. Altogether, five historiographic works that build the researcher s journey through the theme are presented, and amongst them, diverse objects were selected. The study also gathers Salles dialogues with Pará s guitarist and composer Tó Teixeira in the studies about folklore and African descendant music, as well as the historian s struggle for the publication and propagation of his vast work. Ultimately, the dissertation exposes over 50 years of studies about the African descendant theme in Pará, revealing that it was a life project for Vicente Salles